Validation of a helmet-based system to measure head impact biomechanics in ice hockey - Allison, M. A.; Kang, Y. S.; Bolte IV, J. H.; Maltese, M. R.; Arbogast, K. B. (Medicine & Science in Sports & Exercise, 2014)
Purpose: This study aimed to quantify differences between head acceleration measured by a helmet-based accelerometer system for ice hockey and an anthropometric test device (ATD) to validate the system`s use in measuring on-ice head impacts.